A Behavioral Test of Accepting Benefits that Cost Others: Associations with Conduct Problems and Callous-Unemotionality - Sakai, Joseph T.; Dalwani, Manish S.; Gelhorn, Heather L.; Mikulich-Gilbertson, Susan K.; Crowley, Thomas J. (PloS one, 2012)
Youth with conduct problems (CP) often make decisions which value self-interest over the interests of others. Self-benefiting behavior despite loss to others is especially common among youth with CP and callous-unemotional traits (CU). Such behavioral tendencies are generally measured using self- or observer-report. We are unaware of attempts to measure this tendency with a behavioral paradigm. In our AlAn's (altruism-antisocial) game a computer program presents subjects with a series of offers in which they will receive money but a planned actual charity donation will be reduced; subjects decide to accept or reject each offer. We tested (1) whether adolescent patients with CP (n = 20) compared with adolescent controls (n = 19) differed on AlAn's game outcomes, (2) whether youths with CP and CU differed significantly from controls without CP or CU, and (3) whether AlAn's game outcomes correlated significantly with CP and separately, CU severity. Patients with CP and CU compared with controls without these problems took significantly more money for themselves and left significantly less money in the charity donation; AlAn's game outcomes were significantly correlated with CU, but not CP. In the AlAn's game adolescents with conduct problems and CU traits, compared with controls without CP/CU, are disposed to benefit themselves while costing others even in a novel situation, devoid of peer influences, where anonymity is assured, reciprocity or retribution are impossible, intoxication is absent and when the "other" to be harmed is considered beneficent. AlAn's game outcomes are associated with measures of CU. Results suggest that the AlAn's game provides an objective means of capturing information about CU traits. The AlAn's game, which was designed for future use in the MRI environment, may be used in studies attempting to identify the neural correlates of self-benefiting decision-making.